2010
DOI: 10.1186/1476-069x-9-6
|View full text |Cite
|
Sign up to set email alerts
|

Air pollution exposure during pregnancy and reduced birth size: a prospective birth cohort study in Valencia, Spain

Abstract: BackgroundMaternal exposure to air pollution has been related to fetal growth in a number of recent scientific studies. The objective of this study was to assess the association between exposure to air pollution during pregnancy and anthropometric measures at birth in a cohort in Valencia, Spain.MethodsSeven hundred and eighty-five pregnant women and their singleton newborns participated in the study. Exposure to ambient nitrogen dioxide (NO2) was estimated by means of land use regression. NO2 spatial estimati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
144
3
10

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(164 citation statements)
references
References 42 publications
7
144
3
10
Order By: Relevance
“…In fully adjusted random-effects meta-analyses a 10 μg/m 3 increase in PM 10 was associated with decreased term birthweight (-8.9g; 95%CI-13.2 to -4.6) [3]. Similarly to our analysis, but based on NO 2 concentration in ambient air, results of the Ballester study revealed that pollution was associated with change in birth length of -0.3 cm (95%CI-0.5 to -0.03) [17].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…In fully adjusted random-effects meta-analyses a 10 μg/m 3 increase in PM 10 was associated with decreased term birthweight (-8.9g; 95%CI-13.2 to -4.6) [3]. Similarly to our analysis, but based on NO 2 concentration in ambient air, results of the Ballester study revealed that pollution was associated with change in birth length of -0.3 cm (95%CI-0.5 to -0.03) [17].…”
Section: Discussionsupporting
confidence: 78%
“…Results of several analyses performed based on a subsample of REPRO_PL, concerning the prenatal exposure to polycyclic aromatic hydrocarbons (PAH) (based on variety of metabolites) and its impact on pregnancy outcomes and children's health were published earlier [17][18][19][20]. Those analyses in consistency to PM10 assessment indicate that Polish pregnant women suffer from a higher PAH exposure level than those in other western countries with living in the city centres, usage of coal for residential heating and passive smoking as significant predictors of PAH metabolites [18].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest an association between VLBW (below 1500g) and maternal exposures to high levels of sulfur dioxide [46,60]. Increased risk of intrauterine growth retardation was observed also in case of maternal exposure to nitrogen dioxide during the first month of pregnancy [65]. An association between exposure to levels of nitrogen dioxide above 40 µg/m 3 during the first trimester of pregnancy and a reduction in birth weight was found [66].…”
Section: The Adverse Effects Of Air Pollution On Pregnancy Outcomes Amentioning
confidence: 69%
“…Payne-Sturges et al (2004) compared the measured and modelled exposure levels of VOCs in GIS environment. Many studies have used the spatial analytical function of GIS in studying the atmospheric environment of cities by integrating GIS with atmospheric environmental models (Wu et al 2011;Ballester et al 2010;Aguilera et al 2009;An et al 2008;Tang and Wang 2007).…”
Section: Introductionmentioning
confidence: 99%